2018
DOI: 10.3133/sim3411
|View full text |Cite
|
Sign up to set email alerts
|

Geologic map of the Castle Rock 7.5' quadrangle, Arizona and California

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit https://www.usgs.gov/ or call 1-888-ASK-USGS (1-888-275-8747).For an overview of USGS information products, including maps, imagery, and publications, visit https://store.usgs.gov.To order USGS information products, visit https://store.usgs.gov/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Multiple post-Bullhead deposits (e.g., House, 2016;Crow et al, 2018a;House et al, 2018) have been identified in the lower Colorado River corridor ( Fig. 3).…”
Section: ■ Background Lower Colorado River Evolution and Depositsmentioning
confidence: 99%
“…Multiple post-Bullhead deposits (e.g., House, 2016;Crow et al, 2018a;House et al, 2018) have been identified in the lower Colorado River corridor ( Fig. 3).…”
Section: ■ Background Lower Colorado River Evolution and Depositsmentioning
confidence: 99%
“…The largest of these water bodies, which occupied the Blythe basin and adjacent areas, covered over 10 000 km 2 (Spencer et al, 2013), almost twice the size Figure 1. Simplified stratigraphic and geomorphic relationships of Neogene formations exposed in the lower Colorado River basin (after Buising, 1990;Howard et al, 2015;Crow et al, 2019a). Ages for the Palo Verde alluvium (Late Pleistocene; Lundstrom et al, 2008) and the Riverside alluvium (Early(?)…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this enigmatic history, the Bouse Formation, as well as the alluvial deposits that overlie it (e.g., Bullhead Alluvium, Howard et al, 2015;Chemehuevi Formation, Malmon et al, 2011;and Blythe Alluvium, Block et al, 2019; Fig. 1), house an outstanding and largely still untapped record of the history of both the CR since the Pliocene and climatic conditions during the early Pliocene.…”
Section: Introductionmentioning
confidence: 99%